Amorphous and Porous Tungsten Oxide Films for Fast‐Switching Dual‐Band Electrochromic Smart Windows. Issue 1 (28th October 2022) - Zhang, Shengliang; Peng, Yutao; Zhao, Jing; Fan, Zengjie; Ding, Bing; Lee, Jim Yang; Zhang, Xiaogang; Xuan, Yimin
Abstract: Dual‐band electrochromic smart windows with dynamic and independent control of near‐infrared (NIR) and visible (VIS) light transmittance can notably reduce the carbon footprint of buildings and improve the occupants' visual and thermal comfort. The dual‐band response is often generated by the phase transition of crystalline electrochromic materials. However, the phase‐transition of crystalline materials is kinetically sluggish, resulting in a long response time. Herein, a fast‐switching dual‐band electrochromic smart window based on a single‐component amorphous and porous tungsten oxide (AP‐WO3 ) cathode without the slow phase‐transition process is demonstrated. The amorphous and porous structure of WO3 not only significantly improves the ion transport, but also provides a large surface area for Li + adsorption that gives rise to a tunable surface plasmon resonance (SPR) in the NIR range. Consequently, the single‐component AP‐WO3 film can modulate the NIR and VIS light transmittance independently and effectively through three distinct modes with high optical modulation, fast switching speed, high bistability, and good cycling stability. The prototype dual‐band electrochromic device assembled by AP‐WO3 cathode also delivers an impressive dual‐band electrochromic performance with fast‐switching speed (6.4 s for coloration and 7.2 s for bleaching). Abstract : A dual‐band electrochromic smart window assembled from single‐component amorphous and porous tungsten oxide cathode not only successfully overcomes the issue of slow switching speed of the current dual‐band electrochromic windows, but also delivers the independent control of visible light and near‐infrared with impressive electrochromic performance, which can significantly reduce the carbon footprint of buildings.